Information Technology and Decision Support in Small and Medium Companies in Lithuania - Skyrius, Rimvydas (Ekonomika, 1999)
Under the conditions of transition economy a lot of newly emerged businesspersons and businesses, small and medium companies in particular. keep encountering various activity problems and problem situations up to the matter of their survival. These situations are influenced by various internal and external factors. Under such conditions, the management of activities requires substantial flexibility and agility. For these purposes, numerous management resources and methods are put into use, information technology (IT) being one of the most widespread and important.The aim of this article is to examine the results of a survey conducted in small and medium companies and organizations in Lithuania and USA, allowing a closer look into the problems of IT use, with special attention given to supporting decisions in problem situations and unstructured conditions. This examination facilitates definition of influences on the use of decision support technologies in management activities of small and medium companies. The article covers various aspects of IT use - applications in use, critical activities and problems, sources of decision information, processing modes, convenience of decision support software. The article is concluded by the possible research directions in this area.